RAREST COMBINATION OF BASILAR SKULL FRACTURE AND AORTIC LACERATION COMPLICATING PERTHE’S SYNDROME (Journal of Forensic Medicine & Toxicology, 2018)
People are casual about safety measures working beneath vehicles while checking faults or doing servicing and repair jobs. Fatalities may occur with heavy weights falling over chest in these cases. We report combination of basilar skull fracture and aortic laceration complicating Perthe’s Syndrome. Case illustrates instantaneous death consequent upon traumatic asphyxia related to failure of an under capacity hydraulic jack.
Keywords: Perthe’s syndrome; Traumatic asphyxia; Masque ecchymotique; Aortic laceration; Basilar Skull Fracture